How is the Social Community of Malang City? Index Study and Performance Analysis - Prastiwi, Lustina Fajar; Lestari, Trianingsih Eni; Saadiyah, Risa; Bajar, Jayson Troy Ferro; Kawaye, Hopkins Henry (JAMPE (Journal of Asset Management and Public Economy), 2025)
The purpose of this study was to determine the Community Development Index (IPMas) of Malang City in 2024 using Importance Performance Analysis (IPA). IPMas can be seen from the Tolerance Index, Mutual Cooperation Index, and Sense of Security Index. The result is that overall IPMas Malang City got a score of 87.56%. This value tends to remain the same but can increase if various programs are implemented properly related to the cooperation index, tolerance index, and sense of security index. Malang City has realized a friendly city by paying attention to aspects of tolerance, mutual cooperation, and adequate sense of security. The contribution of this paper is to explain the performance of the Malang city government in the social community sector. The success of the regional government's performance can be measured not only by economic growth, but also by the influence of government performance on the community development index.